STUDY OF HADITH IN IBN ABI JAMRAH'S MUKHTASAR MANUSCRIPT OF SAHIH AL-BUKHARI - Nanda Zahra Rasyiffah; Hudaidah Hudaidah; Risa Marta Yati (Jurnal Studi Hadis Nusantara, 2025)
The Mukhtasar of Ibn Abi Jamrah on Sahih al-Bukhari is a condensed hadith compilation intended to present prophetic traditions in a concise and accessible form. This study examines selected hadiths in the manuscript, focusing on three main themes: the virtue of reciting basmalah, the ethical significance of smiling, and descriptions of human conditions on the Day of Judgment. It also analyzes the simplification of the chains of transmission (sanad) as a distinctive methodological feature of the text. This research employs a qualitative library-based method using hadith content analysis. The findings indicate that the hadiths contained in the Mukhtasar are primarily derived from Sahih al-Bukhari but are presented in a shortened format, often without complete chains of narration. Such simplification reflects a pedagogical orientation aimed at facilitating understanding, memorization, and practical application of Islamic teachings among a broader audience. In terms of substance, the hadiths on basmalah emphasize divine protection and blessings in everyday activities, the hadiths on smiling highlight the importance of social ethics and moral conduct, and the hadiths concerning the Day of Judgment strengthen belief in the afterlife and divine justice. Overall, this study demonstrates that the Mukhtasar of Ibn Abi Jamrah functions not merely as a summary of hadiths but as a didactic work that contributes to the formation of moral character and spiritual awareness through a simplified yet meaningful presentation of prophetic teachings.